Text and context in the modern history of Chinese religions: redemptive societies and their sacred texts - Clart, Philip; Ownby, David; Wang, Chien-chuan (Religion in Chinese societies, 2020)
"Text and Context in the Modern History of Chinese Religions: Redemptive Societies and Their Sacred Texts is an edited volume (Philip Clart, David Ownby, and Wang Chien-chuan) offering eight essays on the modern history of redemptive societies in China and Vietnam by an international cast of scholars. The focus of the volume is on the texts produced by the various groups, examining questions of textual production (spirit-writing), textual traditions (how to "modernize" traditional discourse), textual authority (the role of texts in making a master a master), and the distribution of texts (via China's experience of "print capitalism"). Throughout, the goal is to explore in depth what some scholars have called the most vital aspect of Chinese religion during the Republican period"--